Analysis of Taxpayer Compliance in the Implementation of the Self-Assessment System in Indonesia: Legal Challenges and Tax Modernization Solutions - Athirah Zahrah; Adelina; Chairun Nissa Eprianty; Nabilah Eka Putri; Siti Adinda Puspita (Jurnal Sahabat ISNU SU, 2024)
Taxes play a crucial role as the main pillar of financing national development and government operations in Indonesia. To promote fiscal independence, the government implements the Self-Assessment System, which grants taxpayers the authority to calculate, pay, and report their taxes independently. However, in practice, the level of voluntary compliance is still hindered by limited tax literacy and the existence of tax avoidance practices. This study aims to examine the implementation mechanism of the Self-Assessment System, identify the factors that hinder taxpayer compliance, and formulate strategies to strengthen compliance within the framework of Indonesia’s positive law. This research employs a normative juridical method using statutory and conceptual approaches. Secondary data were analyzed descriptively and analytically through deductive legal reasoning. The findings indicate that although tax regulations, such as the Law on General Provisions and Tax Procedures (KUP Law), the Harmonization of Tax Regulations Law (HPP Law), and the Job Creation Law, have provided legal certainty, the effectiveness of the system remains constrained by information asymmetry between tax authorities and taxpayers, as well as unequal digital infrastructure development. Efforts to improve taxpayer compliance require an integrative approach through continuous fiscal education, modernization of risk-based tax administration systems (core tax system), and transparent inter-agency supervision. This study contributes theoretically to the development of a more adaptive and accommodative fiscal legal policy in Indonesia.